A novel approach to treating opioid use disorders: Dual agonists of glucagon-like peptide-1 receptors and neuropeptide Y2 receptors. (December 2021) - Merkel, Riley; Moreno, Amanda; Zhang, Yafang; Herman, Rachel; Ben Nathan, Jennifer; Zeb, Sana; Rahematpura, Suditi; Stecyk, Kamryn; Milliken, Brandon T.; Hayes, Matthew R.; Doyle, Robert P.; Schmidt, Heath D.
Highlights: GLP-1R agonists attenuate opioid-mediated behaviors. Adverse effects related to GLP-1R agonists could limit compliance in patients with OUD. Dual agonism of GLP-1Rs and Y2Rs reduce opioid taking and seeking. GLP-1R/Y2R activation produces less adverse effects than GLP-1R monotherapy. Abstract: The widespread misuse of opioids and opioid use disorder (OUD) together constitute a major public health crisis in the United States. The greatest challenge for successfully treating OUD is preventing relapse. Unfortunately, there are few FDA-approved medications to treat OUD and, while effective, these pharmacotherapies are limited by high relapse rates. Thus, there is a critical need for conceptually new approaches to developing novel medications to treat OUD. Here, we review an emerging preclinical literature that suggests that glucagon-like peptide-1 receptor (GLP-1R) agonists could be re-purposed for treating OUD. Potential limitations of this approach are also discussed along with an alternative strategy that involves simultaneously targeting and activating GLP-1Rs and neuropeptide Y2 receptors (Y2Rs) in the brain using a novel monomeric dual agonist peptide. Recent studies indicate that this combinatorial pharmacotherapy approach attenuates voluntary fentanyl taking and seeking in rats without producing adverse effects associated with GLP-1R agonist monotherapy alone. While future studies are required to comprehensively determine the behavioral effects of GLP-1R agonists and dual agonists of GLP-1Rs and Y2Rs in rodent models of OUD, these provocative preclinical findings highlight a potential new GLP-1R-based approach to preventing relapse in humans with OUD.